Multilateral treaties deposited with the secretary-general: Status as at 31 December 2006 - United Nations (United Nations, 2014)
This publication provides information on the status of major multilateral instruments deposited with the Secretary-General of the United Nations (as of 31 December 2006). It covers issues such as human rights, disarmament, commodities, refugees, environment and the Law of the Sea.